Optical diagnostics on the effects of fuel properties and coolant temperatures on combustion characteristic and flame development progress from HCCI to CDC via PPC. (1st June 2020) - Cui, Yanqing; Liu, Haifeng; Geng, Chao; Tang, Qinglong; Feng, Lei; Wang, Yu; Yi, Wentao; Zheng, Zunqing; Yao, Mingfa
Abstract: The effects of fuel properties and coolant temperatures on combustion characteristic and flame development progress were investigated in an optical engine. The combustion mode was transited from homogeneous charge compression ignition (HCCI) to conventional diesel combustion (CDC) via partially premixed combustion (PPC) by changing the start of injection (SOI) timings from early to late injections. The main fuel properties were separated by using diesel, n-heptane, iso-octane, n-butanol and their mixtures. Diagnostics included conventional in-cylinder pressure and heat-release analysis, high-speed imaging and the spatially integrated flame luminosity intensity. The results show that the variation of combustion phasing (CA50) is more sensitive to the variation of fuel properties of cetane number, latent heat and atomic oxygen at all tested combustion modes. However, fuel physical properties such as dilution, viscosity and volatility only have significant effects at HCCI, while minor effects at PPC and CDC. Fuel properties have minor effects on flame development progress, but significant effects on maximum value of natural flame luminosity intensity. At SOI-15, the main factor to reduce the maximum value of natural flame luminosity intensity is the dilution, viscosity and volatility (40%) followed by the latent heat and the atomic oxygen (18.5%) and cetane number (1.6%). At SOI-5, the main factor is the cetane number (44.1%) followed by the latent heat and the atomic oxygen (36.2%) and dilution, viscosity and volatility (2.4%). Coolant temperature significantly influences combustion phasing and peak in-cylinder pressure and heat release rate at early injection timings, but these effects weaken at late injection timings.